Improving permeability of coal seams by freeze-fracturing method: The characterization of pore structure changes under low-field NMR - Yunpei Liang; Youting Tan; Fakai Wang; Yongjiang Luo; Zhiqiang Zhao (Energy Reports, 2020)
The method of improving permeability of coal seams by freeze-fracturing is presented to accelerate the diffusion of coalbed gas into exploited wells. The pore structure of coal sample changes caused by freeze-fracturing were characterized by nuclear magnetic resonance (NMR) and scanning electron microscopy (SEM), and a permeability-calculation model was employed to estimate the permeability of coal sample. The pore size distribution, porosity, and permeability of coal before and after freezing were analyzed. Results show that freeze-fracturing can complicate the coal pore structure, and its complexity is positively correlated with the freezing temperature and coal moisture content. The main manifestation is the growth and expansion of coal pores, with higher pore connectivity, generation of gas seepage pores with pore diameter > 100~nm, and expansion of original pores into larger ones. By comparing the connectivity and seepage space of the pore structure of coal before and after freezing, it is concluded that freeze-fracturing can promote the coal seam permeability significantly, which is beneficial for the exploitation of coalbed gas.
Keywords: 330; Coal pore structure; Freeze-fracturing; Nuclear magnetic resonance; Permeability